A Double‐Armed, Hydrophilic Transition Metal Complex as a Paramagnetic NMR Probe. (13th August 2019) - Miao, Qing; Liu, Wei‐Min; Kock, Thomas; Blok, Anneloes; Timmer, Monika; Overhand, Mark; Ubbink, Marcellus
Abstract: Synthetic metal complexes can be used as paramagnetic probes for the study of proteins and protein complexes. Herein, two transition metal NMR probes (TraNPs) are reported. TraNPs are attached through two arms to a protein to generate a pseudocontact shift (PCS) using cobalt(II), or paramagnetic relaxation enhancement (PRE) with manganese(II). The PCS analysis of TraNPs attached to three different proteins shows that the size of the anisotropic component of the magnetic susceptibility depends on the probe surroundings at the surface of the protein, contrary to what is observed for lanthanoid‐based probes. The observed PCS are relatively small, making cobalt‐based probes suitable for localized studies, such as of an active site. The obtained PREs are stronger than those obtained with nitroxide spin labels and the possibility to generate both PCS and PRE offers advantages. The properties of TraNPs in comparison with other cobalt‐based probes are discussed. Abstract : Zwei Arme sind besser als einer : Der stabile, zweiarmige Komplex Co II ‐TraNP1 verursacht eine Pseudokontakt‐Signalverschiebung, wenn er an das T4‐Lysozym K147C/T151C bindet. Diese Verschiebung lässt sich für die biomolekulare NMR‐Spektroskopie ausnutzen.